Zhongguancun Model: Driving the Dual Engines of Science & Technology and Capital - Dong, Xiaoying; Hu, Yanni; Yin, Weidong; Kuo, Estela (Springer Nature Singapore : Imprint: Springer, 2019)
XXII, 338 p. 124 illus., 116 illus. in color.